ANALISIS EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DI BAGIK MANIS KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR TAHUN 2019 - Elok Aulia Rizqi Maligan; Muhammad Syukri; Saepul Pahmi; Wahyu Kurniawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
This study aims to determine the effectiveness of managing village funds sourced from APBDes in Bagik Manis Village, Sambelia District, East Lombok Regency, the data collection method in this study uses qualitative methods with a descriptive approach. The data used in this study are primary data and secondary data originating from budget realization in Bagik Manis Village, Sambelia District, East Lombok Regency in 2019. The effectiveness of the management of village fund allocations is in the effective category, both seen from the effectiveness ratio according to the Ministry of Home Affairs and the effectiveness measure from the results of interviews in Bagik Manis Village, Sambelia District, East Lombok Regency as the recipient of ADD funds is fully responsible for implementing and reporting ADD finances in the village for the benefit of the community. It's just that certain programs or fields need to be improved in terms of funds and attention so that there is no overlap in each field, and not only the transparency of village officials to the community regarding the allocation of village funds makes community participation less in government policies. However, the village government is able to minimize these obstacles so that they are able to complete their tasks properly.